Development Status of Higher Education in Northern Indian: A Review Study - Chaman Verma (Lectito Journals, 2017)
In development of any country depends upon higher educational status. India is fast growing country in the field of education and technology. Most of IT engineers are deputed in world's most IT companies. It has been possible because of strong development higher education system in India. This paper focuses on the comparative study of higher educational universities located in Haryana and Punjab. The findings of this paper explores that government has emphasized on privatization of higher education in two states.